2018
DOI: 10.1186/s12957-018-1378-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of miR-182-5p in lung squamous cell carcinoma: a study combining data from TCGA, GEO, and RT-qPCR validation

Abstract: BackgroundMiR-182-5p, as a member of miRNA family, can be detected in lung cancer and plays an important role in lung cancer. To explore the clinical value of miR-182-5p in lung squamous cell carcinoma (LUSC) and to unveil the molecular mechanism of LUSC.MethodsThe clinical value of miR-182-5p in LUSC was investigated by collecting and calculating data from The Cancer Genome Atlas (TCGA) database, the Gene Expression Omnibus (GEO) database, and real-time quantitative polymerase chain reaction (RT-qPCR). Twelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 53 publications
4
23
0
Order By: Relevance
“…In the present study, ADAMTS9-AS2/has-mir-182/RECK axis and ADAMTS9-AS2/hsamir-182/CITED2 axis may construct a ceRNA network were closely to play a significant role in the progression of lung squamous cell carcinoma. Hsa-mir-182 upregulation greatly contributes to lung squamous cell carcinoma [46], which is the same as our results. A previous study shows that TTTY16 may act as a prognostic signature to cluster the patients with LUSC [47].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, ADAMTS9-AS2/has-mir-182/RECK axis and ADAMTS9-AS2/hsamir-182/CITED2 axis may construct a ceRNA network were closely to play a significant role in the progression of lung squamous cell carcinoma. Hsa-mir-182 upregulation greatly contributes to lung squamous cell carcinoma [46], which is the same as our results. A previous study shows that TTTY16 may act as a prognostic signature to cluster the patients with LUSC [47].…”
Section: Discussionsupporting
confidence: 91%
“…Studies also reported that the miRNA miR-182-5p participated in the occurrence and progression of various human cancers [25][26][27][28][29][30]. In previous work, we demonstrated a tumor-promoting effect of upregulated miR-182-5p in lung squamous cell carcinomas (LUSCs) [31].…”
Section: Introductionmentioning
confidence: 72%
“…Isolation and normalization of RNA, and the RT-qPCR were carried out as previously described [31][32][33][34][35][36][37][38]. RNU6B was selected as an endogenous control and reference gene of miR-182-5p [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) has redox homeostasis and can be used in the treatment of lung cancer (Nishimura et al, 2019). NR3C1 is reported to be involved in the pathways related to the biological process of lung cancer, and as a gene marker has a significant correlation with the survival of LUAD (Zhao et al, 2015;Luo et al, 2018). Cathepsin L1, as a protein was encoded by the CTSL1 gene, could reduce the cellular matrix and proteolytic cascades which resulting to promote invasion or metastatic activity (Duffy, 1996;Turk et al, 2012).…”
Section: The Biological Significance Of the Selected Genes In Lung Camentioning
confidence: 99%